Fieldbook of grassland species - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Tropical forage legumes and grasses by Siegfried Legel 1990 335pp ISBN 3 331 00453 7 Deutscher Landwirtschaftsverlag Rheinhardtstr. 14, 1040 Berlin GERMANY